Neurotrophic Factors in Parkinson’s Disease: Clinical Trials, Open Challenges and Nanoparticle-Mediated Delivery to the Brain - Bondarenko, Olesja; Saarma, Mart (Frontiers in Cellular Neuroscience, 2021)
Neurotrophic factors (NTFs) are small secreted proteins that support the development, maturation and survival of neurons. NTFs injected into the brain rescue and regenerate certain neuronal populations lost in neurodegenerative diseases, demonstrating the potential of NTFs to cure the diseases rather than simply alleviating the symptoms. NTFs (as the vast majority of molecules) do not pass through the blood-brain barrier (BBB) and therefore, are delivered directly into the brain of patients using costly and risky intracranial surgery. The delivery efficacy and poor diffusion of some NTFs inside the brain are considered the major problems behind their modest effects in clinical trials. Thus, there is a great need for NTFs to be delivered systemically thereby avoiding intracranial surgery. Nanoparticles (NPs), particles with the size dimensions of 1−100 nm, can be used to stabilize NTFs and facilitate their transport through the BBB. Several studies have shown that NTFs can be loaded into or attached onto NPs, administered systemically and transported to the brain. To improve the NP-mediated NTF delivery through the BBB, the surface of NPs can be functionalized with specific ligands such as transferrin, insulin, lactoferrin, apolipoproteins, antibodies or short peptides that will be recognized and internalized by the respective receptors on brain endothelial cells. In this review, we elaborate on the most suitable NTF delivery methods and envision “ideal” NTF for Parkinson’s disease (PD) and clinical trial thereof. We summarize current possibilities of NP-mediated delivery of NTFs to the brain and discuss whether NPs have impact in improving the properties of NTFs and delivery across the BBB. Emerging delivery approaches and future directions of NTF-based nanomedicine are also discussed.